Pendidikan Kesehatan tentang Kesiapan Identitas pada Remaja di Parak Gadang Timur, Andalas Padang - Rika Sarfika; Uci Ramadhani Anwar; Feri Fernandes (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2020)
Adolescence is a period of attaining identity. If it fails, then Identity Confusion will occur. For adolescents to grow into great generations and vigorous self-defense, adolescents need to achieve optimal identity development. This program aims to stimulate adolescent growth and development to make the readiness of growth and development of identity in adolescents. The activity was carried out on November 27, 2019, at junior high school students at SMPN 9 Padang. A total of 29 teenagers attended the health education provided with lecture and stimulation methods. Before and after attending health education, adolescents fill out questionnaires containing five questions about adolescent knowledge of adolescent growth and development. Knowledge data were processed using t-dependent tests to determine changes in teenage knowledge scores before and after attending health education. The activities showed that the average score of knowledge of adolescents before being given health education was 2.72 and after being given health education was 4.31. Paired sample t-test results showed the value of Pv = 0.000, meaning that there was a significant change between adolescents' knowledge before and after being given health education. Based on the results, it is recommended for nurses at the public health center to continue to conduct health education and socialization about adolescents' growth and development to increase the readiness of adolescent psychosocial growth and development.